1. Prove that 12 + 22 + 32 + β― + ππ2 = ππ(ππ+1)6(2ππ+1) , βππ β β by using the principle of
mathematical induction.
2. Determine the power set of π΄π΄ = {{ππ, ππ},{ππ},{ππ, ππ, ππ}}.
3. Suppose β = {1,2,3, β¦ } is the universal set and π΄π΄ = {π₯π₯: π₯π₯ β€ 6}, π΅π΅ = {π₯π₯: 4 β€ π₯π₯ β€ 9} and
πΆπΆ = {2,3,5,7,8}. Then, find π΄π΄ β© (π΅π΅ β πΆπΆ).
4. Let π΄π΄ = {1,2}, π΅π΅ = {ππ, ππ, ππ} ππππππ πΆπΆ = {ππ, ππ}. Then show that (π΄π΄ Γ π΅π΅) β© (π΄π΄ Γ πΆπΆ) =
π΄π΄ Γ (π΅π΅ β© πΆπΆ).
5. Let π
π
be the equivalence relation on the set π΄π΄ = {1, 2, 3, 4, 5, 6}, given by π
π
=
{(1,1), (1,5), (2,2), (2,3), (2,6), (3,2), (3,3), (3,6), (4,4), (5,1), (5,5), (6,2), (6,3), (6,6)}.
Then, find the partition of π΄π΄ induced by π
π
(i.e., find the quotient set π΄π΄/π
π
).
6. Show that ππ: β β β, ππ(π₯π₯) = 3π₯π₯5+1
is a one-to-one correspondence.
1 answer
For n = 1, we have 12 = 1(1+1)/6(2(1)+1) which is true.
2. Inductive Hypothesis:
Assume that for some k β β, 12 + 22 +...+ k^2 = k(k+1)/6(2k+1).
3. Inductive Step:
We need to show that (k+1)(k+1+1)/6(2(k+1)+1) = 1^2 + 2^2 +...+ k^2 + (k+1)^2.
Starting with the left side:
(k+1)(k+2)/6(2k+3) = (k(k+1) + 2(k+1))/6(2k+3)
= k(k+1)/6(2k+1) + (2(k+1))/(6(2k+3))
= 12 + 22 +...+ k^2 + (2(k+1))/(6(2k+3))
= 12 + 22 +...+ k^2 + (k+1)^2
Therefore, by the principle of mathematical induction, 12 + 22 +...+ n^2 = n(n+1)/6(2n+1) for all n β β.
2. The power set of A = {{a, b}, {c}, {d, e, f}} is {{}, {a, b}, {c}, {d, e, f}, {a, b, c}, {a, b, d, e, f}, {c, d, e, f}, {a, b, c, d, e, f}}. It consists of all possible subsets of A, including the empty set and the set itself.
3. A β© (B β C) means the intersection of A with the symmetric difference of B and C.
B β C = (B βͺ C) \ (B β© C)
= ({x: 4 β€ x β€ 9} βͺ {2,3,5,7,8}) \ ({4,5,6,7,8,9} β© {2,3,5,7,8})
= {x: 4 β€ x β€ 9} \ {5,7,8}
= {4,6,9}
A β© (B β C) = {x: x β€ 6} β© {4,6,9}
= {4,6}
4. (A Γ B) β© (A Γ C) is the intersection of A cross B and A cross C.
(A Γ B) = {(1,a), (1,b), (1,c), (2,a), (2,b), (2,c)}
(A Γ C) = {(1,c), (1,d), (2,c), (2,d)}
(A Γ B) β© (A Γ C) = {(1,c), (2,c)}
A Γ (B β© C) is the cartesian product of A and the intersection of B and C.
(B β© C) = {c}
A Γ (B β© C) = {(1,c), (2,c)}
Therefore, (A Γ B) β© (A Γ C) = A Γ (B β© C).
5. The partition of A induced by R is the set of equivalence classes formed by R.
From the given relation R, we can find the equivalence classes as follows:
[1] = {1, 5}
[2] = {2, 3, 6}
[3] = {2, 3, 6}
[4] = {4}
[5] = {1, 5}
[6] = {2, 3, 6}
Therefore, the partition of A induced by R is {[1], [2], [3], [4], [5], [6]}.
6. To show that f: β β β, f(x) = 3x^5+1 is a one-to-one correspondence, we need to show that it is both injective (one-to-one) and surjective (onto).
Injective:
Assume f(a) = f(b) for some a, b β β.
This means 3a^5+1 = 3b^5+1.
Subtracting 1 from both sides and dividing by 3, we get a^5 = b^5.
Taking the fifth root of both sides, we get a = b.
Therefore, f is injective.
Surjective:
For any y β β, we need to show that there exists an x β β such that f(x) = y.
Let x = ((y-1)/3)^(1/5), then f(x) = 3[((y-1)/3)^(1/5)]^5+1 = y.
Therefore, f is surjective.
Since f is both injective and surjective, it is a one-to-one correspondence.